Intranasal monkeypox marmoset model: Prophylactic antibody treatment provides benefit against severe monkeypox virus disease. - Eric M Mucker; Suzanne E Wollen-Roberts; Adrienne Kimmel; Josh Shamblin; Darryl Sampey; Jay W Hooper (Public Library of Science (PLoS), 2018)
Concerns regarding outbreaks of human monkeypox or the potential reintroduction of smallpox into an immunological naïve population have prompted the development of animal models and countermeasures. Here we present a marmoset model of monkeypox and smallpox disease utilizing a relevant poxvirus via a natural exposure route. We found that 1000 plaque forming units (PFU) of Monkeypox virus was sufficient to recapitulate smallpox disease, to include an incubation period of approximately 13 days, followed by the onset of rash, and death between 15 and 17 days. Temporally accurate manifestation of viremia and oral shedding were also features. The number of lesions ranged from no lesions to 299, the most reported in a marmoset exposed to a poxvirus. To both evaluate the efficacy of our antibodies and the applicability of the model system, marmosets were prophylactically treated with two monoclonal antibodies, c7D11 and c8A. Of three marmosets, two were completely free of disease and a single marmoset died 8 days after the mock (n = 1) or PBS control(s) (n = 2). Evaluation of the serum levels of the three animals provided a possible explanation to the animal succumbing to disease. Interestingly, more females had lesions (and a greater number of lesions) and lower viral burden (viremia and oral shedding) than males in our studies, suggesting a possible gender effect.